DEMOTEC - Quality Assurance Plan - Spyridou, Lia-Paschalia; Manavopoulos, Vasilis (My University, 2021)
The Quality Assurance Plan (QAP) for the DEMOTEC project is written to serve as a handbook for all management processes that are to be followed during the course of the DEMOTEC project, in order to ensure the quality and timely submission of the produced results. The purpose of this document is to set thorough standards and directions for management procedures, roles, and responsibilities and to establish processes for deliverable preparation and peer reviewing. It additionally describes guidelines for internal communication within the Consortium, procedures for quality assessment, a draft dissemination plan and discusses issues of data protection and ownership.
Keywords: Μanagement processes